Pharmacokinetics and pharmacodynamics in antibiotic dose optimization. (2nd January 2016) - Sy, Sherwin KB; Zhuang, Luning; Derendorf, Hartmut
Abstract : Introduction : Identifying the optimized dosing regimen and algorithm is critical in the development of antibiotics. Suboptimal regimens and inappropriate choice of drug give rise to drug-resistant bacteria which have limited the therapeutic utility of many commercially available antimicrobial agents. Strategies to optimize therapy of antimicrobial candidates to speed up the development process are urgently needed. Areas covered : We examined pharmacokinetics and pharmacodynamics of antimicrobial agents with modeling and simulation approaches. The approach that is based on minimum inhibitory concentration to evaluate antimicrobial dosing strategy is widely utilized in drug development. The modeling approach utilizing information from time-kill kinetic studies is a tool that can provide more information on the time-course of bacterial response to a particular dosing regimen. Animal studies of dosing regimens that mimic human pharmacokinetics are another option to evaluate antimicrobial efficacy. Empirical, semi-mechanistic and mechanistic models of bacterial dynamics and development of drug resistance in response to drug therapy are discussed. Expert opinion : Both theories and applications of these approaches provide an overall understanding of how the tools can streamline drug development process and help make crucial decisions. Many opportunities and potentials are presented to incorporate more rigorous integration of PK-PD modeling approaches even at preclinical stage to extrapolate to clinical settings, thus enabling successful trials and optimizing dosing strategies in relevant populations where the drug is mostly used.